The Effect of Guide Imagery Relaxation Techniques on Anxiety Levels of Pre-Op Vitrectomy Patients at Smec Eye Specialist Hospital Medan in 2021 - Syamsul Idris (Science Midwifery, 2022)
Anxiety is an emotional reaction to the perception of danger, either real or imagined. Anxiety is a common reaction to disease because disease is perceived as a general threat to life, health, and the integrity of the body. Anxiety can result in an increase in blood pressure or blood sugar in surgery patients. This type of research is a quasi experiment with a one group pre-post test design. With the aim of knowing to identify the effect of the guide imagery relaxation technique on the anxiety level of pre-op vitrectomy patients at the SMEC Medan Special Eye Hospital in 2021. The population is all pre-op vitrectomy patients at the Medan SMEC Eye Specialist Hospital in 2021, as many as 15 people. Based on the results of the study showed that the anxiety level of pre-op vitrectomy patients before the guide imagery relaxation technique was performed, the majority of respondents experienced severe anxiety (Score 28-42) as many as 8 people (53.3%), and the minority experienced Panic (Score 43-56) as many as 1 person. (6.7%). Then after the guide imagery relaxation technique was performed, the majority of mild anxiety (score 14-20) were 9 people (60%), minority moderate anxiety (score 21-27) were 6 people (40%). The results of the statistical test showed that the mean value of the pre-test was 3.93 and the post-test was 2.33 so that a difference of 1.6 was obtained, then the standard deviation of the pre-test was 1.280 and the post-test value was 0.488, so the difference was 0.792 with a significant p-value of 0.000.